Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/odi.14120
|View full text |Cite
|
Sign up to set email alerts
|

Is OLP potentially malignant? A clue from ZNF582 methylation

Abstract: Oral lichen planus (OLP) is a chronic inflammatory disease with 1%-2% prevalence depending on the global region (Gonzalez-Moles et al., 2020). The OLP clinical diagnosis requires, firstly, the presence of bilateral more or less symmetrical white lesions affecting the buccal mucosa, and/or gingiva, and/or tongue, and/or lip; secondly, the presence with white papular lesions and lace-like network of slightly raised white lines (reticular, annular or linear pattern) with/ without erosions and ulcerations; third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…We would therefore argue that Chiu et al (Chiu et al, 2021) conclusion that OLP is not potentially malignant should not be the basis for the management of patients diagnosed with OLP.…”
Section: Is Oral Lichen Planus Potentially Malignant: a Reply To Yu-w...mentioning
confidence: 93%
See 1 more Smart Citation
“…We would therefore argue that Chiu et al (Chiu et al, 2021) conclusion that OLP is not potentially malignant should not be the basis for the management of patients diagnosed with OLP.…”
Section: Is Oral Lichen Planus Potentially Malignant: a Reply To Yu-w...mentioning
confidence: 93%
“…Latest publicly available meta-analysis estimated the risk of malignancy among OLP sufferers to be in the order of 1-2% (Ramos-García et al, 2021). The authors, Yu-Wei Chiu et al in a recently published article in Oral Diseases claim that OLP is unlikely to be potentially malignant based on their findings on a single biomarker that they examined in 43 clinically diagnosed patients (Chiu et al, 2021). Their main contention is that ZNF582 hypermethylation occurs in patients with oral epithelial dysplasia and OSCC but they did not find high levels methylation of ZNF582 in the OLP group who presented similar ZNF582 level to the normal control group and had a significantly lower level than that in the dysplasia and OSCC groups.…”
Section: Is Oral Lichen Planus Potentially Malignant: a Reply To Yu-w...mentioning
confidence: 99%
“…Studies on the potential for malignant transformation observed a transformation rate of 1.14% 5 . Different studies have searched for genetic markers or similarities in the expression profile of genes that participate in the malignant transformation of OLP into OSCC 6 9 . However, the potential for malignant transformation remains the subject of much analysis and remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Among those hypermethylated genes, ZNF582 was studied rigorously and was selected for biomarker development based on promising findings. The correlation between ZNF582 methylation and oral cancer has been extensively studied in recent years [ 29 , 30 , 32 , 33 , 34 , 35 ]. ZNF582 methylation demonstrated as an effective biomarker for the detection of oral dysplasia and oral cancer via collection of oral scrapings from normal oral mucosa subjects, oral potentially malignant patients, and OSCC patients.…”
Section: Introductionmentioning
confidence: 99%